The Current Viral agents; ZIKA, CHIKUNGUNYA, EBOLA, ENTEROVIRUS D68, MERS CoV, Influenza - Ferhat Gürkan Aslan (Kocaeli Üniversitesi Sağlık Bilimleri Dergisi, 2016)
In this review was mentioned briefly cover of current viral agents that not only to restricted regions of the world but also for our region began to increase of the importance and threaten the health; Zika, Chikungunya, Ebola, Enterovirus d68, MERS and Influenzavirus.